Edukasi Pencegahan Perundungan untuk Merangkul Keberagaman di Satuan Pendidikan - wayan mekarini, wayan mekarini (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Indonesia is a vast archipelago, making diversity a unique asset. However, differences are often used as an excuse for bullying, causing discomfort for victims. Therefore, the MKWK team participated in a bullying prevention program in SMK Triatma Jaya Tabanan. The goal of the activity was to empower participants to avoid potential bullying, whether as victims or perpetrators. The speaker who is also a psychologist, presented the material using various examples and videos. This is expected to have a significant impact on understanding the importance of protecting oneself and others from bullying behavior. Students were introduced to four types of bullying namely physical, verbal, social, and cyber, so they can avoid them and adopt a stance embracing diversity. If there are victims of bullying it can be done five steps such as courageously reprimanding the perpetrator, diverting the perpetrator's attention, inviting others to help, waiting for the situation to subside, and attempting to record the incident. In this assistance, personal safety is the primary consideration. Teachers also received reinforcement in monitoring and processing when bullying occured. This education can be seen as forming a collective awareness to reject bullying actions in order to create a safe and comfortable school environment.